The effect of ideal strategy with formative feedback on conceptual understanding and physics processing skill of XI graders senior high school - Rahmadhani Pratama; Wartono Wartono; Sentot Kusairi (Universitas PGRI Kanjuruhan Malang, 2019)
This research aims at identifying conceptual understanding and Physics scientific processing skill of students in IDEAL learning strategy with formative feedback and IDEAL learning only without formative feedback. It employed semi-experimental design using posttest only control group design. The sampling technique used random sampling. This research took two classes of XI graders of Natural Science classes from SMAN 2 Banjarmasin. The control class was taught by using IDEAL strategy only without formative feedback. While the experimental class was taught by using IDEAL strategy with formative feedback. There is a significant difference of conceptual understanding and Physics scientific processing skill of students between IDEAL strategy with formative feedback and IDEAL strategy without formative feedback. It further affirms that students’ conceptual understanding in the class taught by IDEAL strategy with formative feedback is higher than the other. As well, students’ scientific processing skill in the class taught by IDEAL strategy with formative feedback is higher than the other.